A handbook to the reception of classical mythology - Zajko, Vanda ca. 20./21. Jh.; Hoyle, Helena (Wiley Blackwell handbooks to classical reception, 2017)
"A Handbook to the Reception of Classical Mythology presents a collection of essays that explore a wide variety of aspects of Greek and Roman myths and their critical reception from antiquity to the present day. Reveals the importance of mythography to the survival, dissemination, and popularization of classical myth from the ancient world to the present day Features chronologically organized essays that address different sets of myths that were important in each historical era, along with their thematic relevance Features chronologically organized essays that address different sets of myths that were important in each historical era, along with their thematic relevance Offers a series of carefully selected in-depth readings, including both popular and less well-known examples."--Publisher description